THE RELATIONSHIP BETWEEN FOMO, FOPO, AND YOLO ON TOURISTS VISITING DECISIONS IN PADANG CITY (A Study on Generation Z and Millennials) - Ainun Mardiah (Faculty of Economic and Social Science, Universitas Islam Negeri Sultan Syarif Kasim, 2025)
This study aims to determine the differences in the levels of Fear of Missing Out (FOMO), the level of Fear of Other People’s Opinions (FOPO), You Only Live Once (YOLO) between Generation Z and Millennials on the decision to visit tourists in Padang City, West Sumatra and to determine the influence of FOMO, FOPO, YOLO on the decision to visit tourists in Padang City, West Sumatra. This study was conducted in Padang City, West Sumatra. The population and sample of the study were tourists who had visited Padang City. The number of research samples was 250 respondents, consisting of 125 respondents from Generation Z and 125 respondents from Millennials. The results of the study showed that there were differences in the levels of FOMO, FOPO, YOLO between Generation Z and Millennials. Generation Z showed a higher level of FOMO than Millennials. The Millennial generation shows a higher level of FOPO than Generation Z. The Millennial generation shows a higher level of YOLO compared to Generation Z. The results of the regression analysis prove that Fear of Missing Out (FOMO), Fear of Other People’s Opinions (FOPO), You Only Live Once (YOLO) have a significant influence on the decision to visit tourists in Padang City, West Sumatra in both generations.